Digital Echoes: Unraveling the Transnational Spread of Far-Right Ideologies through the Identitarian Movement's Social Media Strategies - Kuncoro, Hestutomo Restu (Jurnal Studi Diplomasi dan Keamanan, 2024)
The rise of far-right movements globally, exemplified by the Identitarian Movement, underscores the significance of social media in political mobilization and ideological dissemination. This research addresses the question: How does the Identitarian Movement utilize social media affordances to propagate its ideologies transnationally? Through a qualitative case study approach, this study analyzes secondary data from reports, books, and academic databases, focusing on the Identitarian Movement's strategic use of platforms like Twitter, YouTube, Facebook, and Telegram. The findings reveal that the movement exploits social media affordances of visibility, editability, persistence, and association to craft and disseminate high-impact, visually appealing content designed to engage and radicalize audiences. The "Defend Europe" campaign is highlighted as a significant example of these strategies in action. The author argues that understanding these digital tactics is crucial for comprehending the global spread of far-right ideologies and for developing effective counter-extremism strategies. The study concludes that the Identitarian Movement's adept use of social media not only enhances their reach but also solidifies their influence across national borders, posing substantial challenges to democratic institutions and social cohesion.